Hyperglycemia Potentiates Carbonyl Stress-Induced Apoptosis in Naive PC-12 Cells: Relationship to Cellular Redox and Activator Protease Factor-1 Expression - Okouchi, Masahiro; Okayama, Naotsuka; Aw, Tak Y. (Current Neurovascular Research, 2005)
The mechanism(s) of central nervous system complication associated with neurodegenerative disorders such as diabetes is unknown. Previous studies demonstrated that carbonyl stress induced by methylglyoxal (MG) mediates differential apoptosis of rat pheochromocytoma (PC12) cells in the naïve or differentiated transition states. Since chronic hyperglycemia is central to diabetic complications, and poorly differentiated cells are oxidatively more vulnerable, we currently investigated the effect of glycemic status on MG-induced apoptosis in naïve (nPC12) cells focusing on glutathione- to-glutathione disulfide (GSH/GSSG) redox signaling. nPC12 cells were exposed to 25 mM glucose acutely for 24h or chronically for 1 week. A role for glycemic fluctuation was tested in chronic high glucose-adapted cells subjected to acute reduction in glucose availability. Acute hyperglycemia potentiated MG-induced nPC12 apoptosis in accordance with cellular redox (GSH-to-Disulfide (GSSG plus protein-bound SSG)) imbalance. Chronic hyperglycemia exacerbated baseline and MG-induced apoptosis that corresponded to exaggerated loss of cytosolic and mitochondrial redox balance, impaired glucose 6-phosphate dehydrogenase (G6PD) activity, and enhanced basal expression of apoptosis protease activator factor-1 (Apaf-1). Reduced glucose availability in hyperglycemia-adapted nPC12 cells induced by acute lowering of glucose or by dehydroepiandrosterone (DHEA, G6PD inhibitor) further enhanced MG-induced apoptosis in association with greater cytosolic and mitochondrial redox and G6PD impairment and elevated basal Apaf-1 expression. These findings demonstrate that chronic hyperglycemia or acute glucose reduction from the chronic hyperglycemic state potentiates carbonyl stress, which collectively contribute to oxidative susceptibility of poorly differentiated cells such as that which occurs in brain neurons of neurodegenerative disorders like diabetes and Alzheimer's disease.
Keywords: hyperglycemia